2013
DOI: 10.1128/jb.01365-13
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Dependent Mannopine-Inducible Conjugative Transfer of an Agrobacterium Opine-Catabolic Plasmid

Abstract: The Ti plasmid in Agrobacterium tumefaciens strain 15955 carries two alleles of traR that regulate conjugative transfer. The first is a functional allele, called traR, that is transcriptionally induced by the opine octopine. The second, trlR, is a nonfunctional, dominant-negative mutant located in an operon that is inducible by the opine mannopine (MOP). Based on these findings, we predicted that there exist wild-type agrobacterial strains harboring plasmids in which MOP induces a functional traR and, hence, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 94 publications
(122 reference statements)
0
40
0
Order By: Relevance
“…Bacterial conjugation is one of the possible means of horizontal transfer of genetic material and it has been intensively studied in Gram-negative bacteria, in particular in the plant pathogen Agrobacterium tumefaciens due to its pathogenic and biotechnological relevance (e.g., tumor-inducing plasmid Ti) (14)(15)(16). Conjugation has been described for Gram-positive bacteria, with the difference that a somewhat simpler conjugative machinery appears to be required due to the fact that DNA traverses just a single membrane layer (17).…”
mentioning
confidence: 99%
“…Bacterial conjugation is one of the possible means of horizontal transfer of genetic material and it has been intensively studied in Gram-negative bacteria, in particular in the plant pathogen Agrobacterium tumefaciens due to its pathogenic and biotechnological relevance (e.g., tumor-inducing plasmid Ti) (14)(15)(16). Conjugation has been described for Gram-positive bacteria, with the difference that a somewhat simpler conjugative machinery appears to be required due to the fact that DNA traverses just a single membrane layer (17).…”
mentioning
confidence: 99%
“…It appears that the high rates of HGT observed in bacterial biofilms may be attributable to quorum-sensing control of the conjugation and production of exoenzymes, toxins, and other virulence factors, in addition to biofilm formation [247,251,263,307,[315][316][317]. Roseobacter species and other environmental bacteria besides Vibrio associate with marine snow and also produce acyl homoserine lactones.…”
Section: Toxin Evolution In Biofilms and Regulation By Quorum Sensingmentioning
confidence: 99%
“…Since HGT occurs at maximal frequencies when bacterial densities of potential recipients are high [246][247][248][249][250][251], one might ask how genetic exchange can occur in aquatic environments, where some bacteria, such as Vibrio, spend most of their time and where their concentrations are expected to be too low to be conducive to HGT. Studies have shown, however, that bacteria found in marine environments are often adherent to marine animals or particles, such as zooplankton or marine snow [252][253][254].…”
Section: Toxin Evolution and Transmission In Aquatic Environmentsmentioning
confidence: 99%
“…In these four cases, conjugation is strongly controlled, with expression of the transfer genes requiring two exogenous signals (Fuqua & Winans, ; Oger & Farrand, ; Piper, Beck von Bodman, Hwang, & Farrand, ; Wetzel et al., ). The first is a particular opine, a type of novel carbon compound produced by the crown gall tumors induced by pathogenic members of the two genera.…”
Section: Introductionmentioning
confidence: 99%
“…It also carries a full set of genes for uptake and catabolism of the mannityl opines. However, traR is not associated with the mot operon and, while located in the canonical site between traM and the traAFBH operon, traR is, in fact, monocistronic (Wetzel et al., ). Mutational analysis showed that traR of this plasmid is essential for MOP‐dependent induction of the synthesis of the acyl‐HSL QS signal and the resultant conjugative transfer of the element (Wetzel et al., ).…”
Section: Introductionmentioning
confidence: 99%